NOCTURNAL HYPOGLYCEMIA: THE TUMOR YOU DON’T SEE, BUT YOUR BLOOD SUGAR DOES - Tamiyes, Farhan Amat; Ahmad, Mohamad Shamir Shamsher; Sathiaseelan, Kalaivani; Yasin, Nurul Ain Nadhirah Mohd; Woo, Wing Hang (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Non-islet cell tumour hypoglycemia (NICTH) is a rare but potentially life-threatening complication of malignancy, often driven by tumour overproduction of insulin-like growth factor 2 (IGF-2). Diagnosis can be challenging due to non-specific symptoms and limited access to specialised assays. CASE We report the case of an 87-year-old female with no known medical history who presented with reduced consciousness and was found to have symptomatic hypoglycemia with capillary glucose 2.1 mmol/L. She had experienced unexplained hypoglycemic episodes over the past 3 months. During hospitalisation, she showed a pattern of nocturnal hypoglycemia that temporarily resolved with continuous dextrose infusion, fulfilling Whipple’s triad. The laboratory work-up revealed low serum insulin, low C-peptide, low insulin-like growth factor, negative serum sulfonylurea screen and normal random serum cortisol. Unfortunately, IGF-2 measurement was not available. A contrast-enhanced CT (CECT) of the thorax and abdomen exposed a large left lung mass with features suggestive of malignancy. The patient was initiated on glucocorticoid therapy, which led to partial improvement, although nocturnal hypoglycemic episodes persisted. Given her advanced age and overall condition, she declined surgical intervention and opted for conservative management. CONCLUSION This case underscores the importance of considering NICTH in elderly patients with recurrent, unexplained hypoglycemia, particularly when occurring nocturnally. IGF-2 overproduction, typically by large mesenchymal or epithelial tumours, is the underlying reason behind these events. Although surgical resection of the tumour remains the definitive treatment, glucocorticoids and frequent glucose supplementation are used in conservative management.